Determining the biodegradation rate of crude oil using some different bacterial species isolated from soil - Marwa Dawood Suleiman Hamid; Hamid Salman Khamis (International Journal of Medical Toxicology and Legal Medicine, 2025)
The current study aimed to determine the biodegradation rate of crude oil using some different bacterial species isolated from soil.100 mg of contaminated and uncontaminated soil samples used in bioremediation experiments were collected from three areas in Tikrit city, including generator soil, refinery soil, and normal uncontaminated soil. The soil samples (weight: 100 g and depth: 3-12 cm) were collected using dark counters and then transferred to the laboratory. Hydrocarbon materials were added with the prepared nutrient agar medium and left to solidify, then both contaminated and normal soils were placed and incubated for 24 hours at 37 °C. The results showed that the most isolated bacteria was Bacillus spp., which amounted to 80.8% compared to the rest of the genera, as the isolation percentage of the genus Enterobacter was one isolate, at a rate of 7.7%, while the isolation percentage of the genus Acinetobacter was two isolates, at a rate of 11.5%. for biodegradation efficacy, Bacillus thuringiensis showed that the highest degradation percentage was 75% for a concentration of 1% crude oil, while, Bacillus subtilis showed that the highest degradation percentage was 67% for a concentration of 1% crude oil. Bacillus firmus showed that the highest decomposition percentage was 74% for a concentration of 1% crude oil. Bacillus tropicus showed that the highest degradation percentage was 62% for a concentration of 1% crude oil. Bacillus taxishowed that the highest degradation percentage reached 42% for a concentration of 1% of crude oil. Bacillus muralis that the highest degradation percentage was77% for a concentration of 1% crude oil. Bacillus megaterium that the highest degradation percentage reached74% for a concentration of 1% crude oil. Enterobacterhormaechei that the highest degradation degradation rate was 61% for a concentration of 1% crude oil. Acinetobacterlwoffii that the highest tion rate was 61% for a concentration of 1% crude oil. The results of the current study showed the ability of the studied bacteria to biodegrade contaminated crude oil in soil. The most efficient bacterial species in biodegrading crude oil was Bacillus muralis.